Lactobacillus rhamnosus for treating irritable bowel syndrome in children – a systematic review with meta-analysis - Tarnoruda, Joanna; Ruszczyński, Marek; Żółkiewicz, Jakub; Sulej, Luiza; Bożek, Barbara; Hoffmann, Aleksandra (Pediatria Polska - Polish Journal of Paediatrics, 2024)
The objective of the study was to systematically assess whether the oral probiotic Lactobacillus rhamnosus (LGG) improves symptoms of irritable bowel syndrome in children. Four randomised clinical trials met the inclusion criteria, a total of 252 patients. Success of treatment was reported in 50 out of 82 patients (58.82%) from the LGG group, compared with 28 from 82 (34.14%) in the placebo group (p = 0.05). The number of pain episodes was lower in the LGG group compared with the placebo group (n = 117, 95% CI: 1.50 [–2.03; –0.97], p < 0.05). The use of LGG resulted in a decrease in the perception of pain intensity in the study population overall (n = 219, 95% CI: –0.61 [–1.13; –0.09], p < 0.05). A higher dosage of LGG was less effective than a lower dosage in improving the overall treatment success (p = 0.05). The dosage of LGG was not statistically significant in improving pain severity (p = 0.12).